Crystal structure, Hirshfeld surface analysis and interaction energy and DFT studies of 2-(2,3-dihydro-1H-perimidin-2-yl)-6-methoxyphenol - Daouda, Ballo (Acta Crystallogr E Crystallogr Commun, 2020)
The title compound, C(18)H(16)N(2)O(2), consists of perimidine and methoxyphenol units, where the tricyclic perimidine unit contains a naphthalene ring system and a non-planar C(4)N(2) ring adopting an envelope conformation with the NCN group hinged by 47.44 (7)° with respect to the best plane of the other five atoms. In the crystal, O—H(Phnl)⋯N(Prmdn) and N—H(Prmdn)⋯O(Phnl) (Phnl = phenol and Prmdn = perimidine) hydrogen bonds link the molecules into infinite chains along the b-axis direction. Weak C—H⋯π interactions may further stabilize the crystal structure. The Hirshfeld surface analysis of the crystal structure indicates that the most important contributions for the crystal packing are from H⋯H (49.0%), H⋯C/C⋯H (35.8%) and H⋯O/O⋯H (12.0%) interactions. Hydrogen bonding and van der Waals interactions are the dominant interactions in the crystal packing. Computational chemistry indicates that in the crystal, the O—H(Phnl)⋯N(Prmdn) and N—H(Prmdn)⋯O(Phnl) hydrogen-bond energies are 58.4 and 38.0 kJ mol(−1), respectively. Density functional theory (DFT) optimized structures at the B3LYP/ 6–311 G(d,p) level are compared with the experimentally determined molecular structure in the solid state. The HOMO–LUMO behaviour was elucidated to determine the energy gap.